TECHNICAL AND TECHNOLOGICAL SOLUTIONS TO INCREASE THE PRODUCTIVITY OF OIL AND GAS WELLS (European Journal of Emerging Technology and Discoveries, 2024)
This article contains information about wells in the Tegermen mine, their drilling, physical-technological properties of wells, and solutions to their problems. Also, project information and strategic structures of wells are studied.